Preparedness and management of global public health threats at points of entry in Ireland and the EU in the context of a potential Brexit - Máirín Boland; Mary O'Riordan (BMC, 2019)
Abstract Health security in the European Union (EU) aims to protect citizens from serious threats to health such as biological agents and infectious disease outbreaks- whether natural, intentional or accidental. Threats may include established infections, emerging diseases or chemical and radiological agents. Co-ordinated international efforts attempt to minimize risks and mitigate the spread of infectious disease across borders. We review the current situation (March 2019) with respect to detection and management of serious human health threats across Irish borders- and what may change for Ireland if/when the United Kingdom (UK) withdraws from the EU (Brexit). Specifically, this paper reviews international legislation covering health threats, and its national transposition; and EU legislation and processes, especially the relevant European Decision No. 1082/2013/EU of the European Parliament and of the Council on serious cross border threats to health with repeal of Decision No 2119/98/EC. We enumerate European surveillance systems and agencies which relate to port health security; we consider consortia and academic arrangements within the EU framework and established collaboration with the World Health Organization. We describe current Health Services Executive port health structures in Ireland which address preparedness and management of human health threats at points of entry. We appraise risks which Brexit could bring, reviewing literature on shared concerns about these risks, and we evaluate post-Brexit challenges for the EU, and potential opportunities to remain within current structures in shared health threat preparedness and response. It is imperative that the UK, Ireland and the EU work together to mitigate these risks using some agreed joint coordination mechanisms for a robust, harmonised approach to global public health threats at points of entry.